INFORMATION ON THE HISTORY OF DAGESTAN IN AN ANONYMOUS PERSIAN WORK OF 1126 - Timohin, Dmitrij Mihajlovic (History, Archeology and Ethnography of the Caucasus, 2021)
Among the historical and geographical works of the XII century, researchers were less in demand for an anonymous monument, which is dated by scientists to 1126 and is called «Mujmal at-tawarih wa-l-kisas» («a Set of stories and narratives»). Despite the fact that this anonymous work has been known to the scientific world for quite a long time, V. V. Barthold has already given it a detailed description in one of his works, so far we have not seen its translation into European languages, as well as special studies on this monument. Russian and foreign scholars have focused on the description of «Mujmal at-tavarikh» either in the analysis of the corpus of monuments of the XII century, or in General works on the history of Persian literature or Seljuk historiography. In such studies, for obvious reasons, the authors have given «Mujmal at-tawarih» much less attention than it, from our point of view, deserves. At the same time, the anonymous essay, which will be discussed in this article, was analyzed, with rare exceptions, for the content of historical information in it. In the same article, we will be interested in both historical and geographical information that can be found in the framework of «Mujmal at-tavarikh» regarding Dagestan. Note that this kind of research is the first experience, at least we are not aware of other special works of this kind, the analysis of «Mujmal at-tawarih» for the presence of information in this source for the specified region. We will also be interested in possible historiographical connections between this work and earlier Arab-Persian historical and geographical monuments. Given the fact that this monument, as the researchers have already noted, is compiled, it seems to us an important scientific task to identify the above-mentioned connections. We hope that this article will increase the interest of researchers, both directly to «Mujmal at-tavarikh» and to the history of Dagestan in the pre-Mongol period.